PHYTOPLANKTON COMPOSITION AND ITS RELATION TO PEARL OYSTER AQUACULTURE (Pinctada maxima) IN SEKOTONG, WEST NUSA TENGGARA - . Fathurrahman; . Aunurohim; Varian Fahmi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Pearl oyster aquaculture is one of the marine industries that is currently growing in West Nusa Tenggara. Pearl oyster (Pinctada maxima) is a common species of oyster that cultivated in West Nusa Tenggara waters. A suitable location is an important factor for the success of pearl aquaculture industry. It needs a good water quality and supported by appropriate physical parameters for other marine biotas. The aim of this research was to analize phytoplankton composition (biological parameter) and it correlation to the Sekotong water condition for pearl farming production. The result showed that the pearl farming location has good water condition according to physio-chemical parameter and water nutrients. All parameters were in suitable range for the growth and development of pearl oysters. Keywords: pearl farming, phytoplankton, Pinctada maxima, West Nusta Tenggara